2021
DOI: 10.3390/pharmaceutics13071012
|View full text |Cite
|
Sign up to set email alerts
|

An Insight into Biomolecules for the Treatment of Skin Infectious Diseases

Abstract: In assigning priorities, skin infectious diseases are frequently classified as minor when compared to infectious diseases of high mortality rates, such as tuberculosis or HIV. However, skin infections are amongst the most common and prevalent diseases worldwide. Elderly individuals present an increased susceptibility to skin infections, which may develop atypical signs and symptoms or even complicate pre-existing chronic disorders. When the skin fails to correct or inhibit the action of certain pathogenic micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 109 publications
0
16
0
Order By: Relevance
“…Antibiotics can be chemically synthesized or extracted from microbial substances. Their effectiveness is defined based on their ability to target elements within the bacterial cell wall and intracellular space and induce a detectable effect without losing their effectiveness throughout the process [ 19 ]. Studies have reported the ability of bacteriostatic (prevent bacterial growth) and bactericidal (kill bacteria) antibiotics to assist with wound closing by effectively acting against infection-producing microbes.…”
Section: Antimicrobial Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibiotics can be chemically synthesized or extracted from microbial substances. Their effectiveness is defined based on their ability to target elements within the bacterial cell wall and intracellular space and induce a detectable effect without losing their effectiveness throughout the process [ 19 ]. Studies have reported the ability of bacteriostatic (prevent bacterial growth) and bactericidal (kill bacteria) antibiotics to assist with wound closing by effectively acting against infection-producing microbes.…”
Section: Antimicrobial Agentsmentioning
confidence: 99%
“…Most importantly synergisms between antibiotics have been revealed, so that the amount loaded within the fibrous scaffolds required for effective action could be reduced and potential side effects against viable tissues mitigated [ 24 ]. Even though antibiotics continue to be used in DFU care, their repeated and/or improper usage has been known to increase bacterial resistance [ 19 ]. In fact, ≈ 70% of bacteria responsible for wound infections are resistant to at least one type of antibiotic, with many infectious strains revealing resistance against many [ 25 ].…”
Section: Antimicrobial Agentsmentioning
confidence: 99%
“…Essential oils (EOs) are a complex mixture of volatile and aromatic chemical compounds (e.g., terpenes, phenols, alcohols, aldehydes, ethers and ketones) extracted from different parts of plants (e.g., buds, flowers, stems, leaves, seeds, twigs, roots, fruits, bark and wood flowers, seeds, leaves, fruits and roots) [9][10][11][12]. These have the function of defending the host from microbial invasion, manifesting antibacterial, antifungal and insecticide activities, aside from antiviral [13][14][15]. Furthermore, EOs have anti-inflammatory, immunomodulatory and bronchodilatory properties [16].…”
Section: Introductionmentioning
confidence: 99%
“…It also allows for controlled drug release 5 . The skin is an organ open to microorganisms, and bacteria, fungi and viruses are among the pathogens that cause skin infections 6, 7 . Due to the limited success of conventional dosage forms in skin infections, intensive studies are carried out on innovative drug delivery systems including microemulsions, liposomes, nanoparticles, nanofibers and micelles 8, 9 .…”
Section: Introductionmentioning
confidence: 99%